Effects of the ketogenic diet on skin—potential benefits and risks - Chylińska, Natalia; Maciejczyk, Mateusz (Frontiers in Nutrition, 2025)
In recent years, interest in the impact of diet on the skin has increased significantly, and dietary interventions are now considered an essential part of managing certain dermatological conditions. Among them, the ketogenic diet (KD) has gained particular attention. KD is a high-fat, very low-carbohydrate, and moderate-protein dietary approach that induces ketosis, defined by serum ketone body concentrations exceeding 0.5 mmol/L. Although initially developed for the treatment of drug-resistant epilepsy in children, its applications have broadened over time. Current evidence on KD and the skin remains limited, focusing mainly on inflammatory skin diseases such as acne, psoriasis, and hidradenitis suppurativa (HS), as well as cutaneous melanoma. In this review, we summarize the existing data on these conditions and discuss the molecular mechanisms underlying the potential effects of KD, including anti-inflammatory and antioxidant pathways, modulation of signaling cascades, and interactions with the gut microbiota. Finally, we also address the reported adverse effects of KD on the skin.